Investigating the factors influencing the acceptance of fully autonomous cars - Ahmed Ziad Benleulmi; Thorsten Blecker (Digitalization in Supply Chain Management and Logistics: Smart and Digital Solutions for an Industry 4.0 Environment. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 23, 2017)
Once thought of as a product of science fiction, self-driving cars are discussed today as an unavoidable means towards improving transportation systems. In fact, many car manufacturers have announced their plans to deploy highly autonomous cars as soon as 2020; according to the Society of Automotive Engineers (SAE) these vehicles are capable of reacting 'even if the human driver does not respond appropriately to the request to intervene (SAE level 4)'. There is however a long way to go before fully autonomous cars (SAE level 5) - where pedals and steering wheels are forgone and limitations to driving during severe weather or in unmapped areas are surmounted - are produced. Herein, the overall aim is to study the drivers and inhibitors of autonomous cars' acceptance across cultures with a special focus on the different risks that might deter consumers from using highly and/or fully autonomous cars. After an extensive reviewing of previous works, a research model based on UTAUT2 was developed and accordingly an online survey was conducted in the US and in Germany; 313 valid answers were collected and analyzed. The findings presented here have serious implications both on the academic field as well as the industry, especially in regards to the roles that risks, culture and gender play in the acceptance of fully autonomous cars.
urn:nbn:de:gbv:830-88217498; 10419/209192; https://econpapers.repec.org/RePEc:zbw:hiclpr:23
Keywords: 650; fully autonomous cars; technology acceptance models; PLS SEM